Musik und Befreiung: Augustinus De musica - Albrecht, Michael von (International journal of musicology, 1994)
Augustine's little known treatise On Music consists of two unequal parts: Books 1-5 treat meter and rhythm technically, the Sixth Book gives a psychological account of the perception of rhythm as an activity of the soul and ends in describing creation and history as a (quasi evolutionary) process in terms of musical rhythm. The aim of the article is to show the unity of the work and single out its leading ideas, most of which are carefully prepared as early as in Book 1. A first crucial theme is liberation through knowledge. Like a musicologist rather than a practical musician, the student of 'liberal' arts has to reflect on music in scientific terms. The dialogue form mirrors his way to truth and liberation. Second, in the field of esthetics, Augustine's description of creation in terms of music may have encouraged others to speak of music in terms of creation. He connected both spheres differently: for him, music was born as a spontaneous expression of joy and praise in an intelligent observer struck by the beauty of the rhythms in God's creation. Finally, as far as method is concerned, for Augustine, the De musica was a stepping stone towards a surprisingly modern philosophy of time and a general theory of signs and interpretation which was applicable to both nature and art. Musical rhythm turned out to be a key to both.
Elektronische Reproduktion der Druckausgabe
Gesehen am 28.07.2023
Mit englischer Zusammenfassung